PENGARUH MEDIA EDUKASI ULAR TANGGA “SERU” TERHADAP PENGETAHUAN KONSUMSI BUAH DAN SAYUR PADA ANAK PRA SEKOLAH DI PAUD KOTA CIMAHI (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: Developing countries in the health sector are undergoing epidemiological transitions including degenerative diseases. Degenerative diseases can occur, one of which is due to lifestyle changes such as reduced public interest in consuming fruits and vegetables. According to Riskesdas data in 2018 in Indonesia, the lack of fruit and vegetable consumption in the population aged ≥5 years is 95.5%, West Java is 98.8% and Cimahi City is included in the city that is still low in fruit and vegetable consumption. Purpose: Knowing the influence of the snakes and ladders educational media